(untitled) (Journal of the College of Basic Education, 2022)
This research is concerned with the study of farewell poetry in Andalusia, the era of the Almohads and Bani Al-Ahmar, in terms of aspectsThree technical, formed the main headings of three topics, preceded by an introduction. The introductory title is (A glimpse of poetryAl-Wada` in al-Andalus, the era of the Almohads and the Bani al-Ahmar, and as for the investigations, it is the first topic: the method,And the second topic: the graphic image, and the third topic: the internal rhythm. The research ended with a conclusion, which was written downIt contains the most important findings. Perhaps the most prominent of them:1. The research showed that the farewell poets succeeded in improving their texts, through diversifying the styles they usedThey used it like interrogative, request, call, and others. And their choice of these methods came;